CLK2 in GABAergic neurons is critical in regulating energy balance and anxiety-like behavior in a gender-specific fashion - Norberto, Sónia; Assalin, Heloisa Balan; Guadagnini, Dioze; Tobar, Natália; Boer, Patrícia Aline; Kang, Min-Cheol; Saad, Mario Jose Abdalla; Kim, Young-Bum; Prada, Patricia Oliveira (Frontiers in Endocrinology, 2023)
Introduction Cdc2-like kinase (CLK2) is a member of CLK kinases expressed in hypothalamic neurons and is activated in response to refeeding, leptin, or insulin. Diet-induced obesity and leptin receptor-deficient db/db mice lack CLK2 signal in the hypothalamic neurons. The neurotransmiter gamma-aminobutyric acid (GABA) is among the most prevalent in the central nervous system (CNS), particularly in the hypothalamus. Given the abundance of GABA-expressing neurons and their potential influence on regulating energy and behavioral homeostasis, we aimed to explore whether the deletion of CLK2 in GABAergic neurons alters energy homeostasis and behavioral and cognitive functions in both genders of mice lacking CLK2 in Vgat-expressing neurons (Vgat-Cre; Clk2loxP/loxP) on chow diet. Methods We generated mice lacking Clk2 in Vgat-expressing neurons (Vgat-Cre; Clk2loxP/loxP) by mating Clk2loxP/loxP mice with Vgat-IRES-Cre transgenic mice and employed behavior, and physiological tests, and molecular approaches to investigate energy metabolism and behavior phenotype of both genders. Results and discussion We showed that deletion of CLK2 in GABAergic neurons increased adiposity and food intake in females. The mechanisms behind these effects were likely due, at least in part, to hypothalamic insulin resistance and upregulation of hypothalamic Npy and Agrp expression. Besides normal insulin and pyruvate sensitivity, Vgat-Cre; Clk2loxP/loxP females were glucose intolerant. Male Vgat-Cre; Clk2loxP/loxP mice showed an increased energy expenditure (EE). Risen EE may account for avoiding weight and fat mass gain in male Vgat-Cre; Clk2loxP/loxP mice. Vgat-Cre; Clk2loxP/loxP mice had no alteration in cognition or memory functions in both genders. Interestingly, deleting CLK2 in GABAergic neurons changed anxiety-like behavior only in females, not males. These findings suggest that CLK2 in GABAergic neurons is critical in regulating energy balance and anxiety-like behavior in a gender-specific fashion and could be a molecular therapeutic target for combating obesity associated with psychological disorders in females.